Impact of Muslim Holy Days on Asian stock markets: An empirical evidence - Irfan Ali; Waheed Akhter; Namrah Ashraf (Cogent Economics & Finance, 2017)
This study investigated the impact of Muslim Holy Days on daily stock returns of Asian financial markets for a period of 2001-2014. These markets include Pakistan, Bahrain, Saudi Arabia, and Turkey. The study has tried to isolate the effect of Gregorian calendar anomalies from Muslim Holy Days to certify that the documented effect is actually a result of Muslim Holy Days rather than Gregorian calendar anomalies. Pooled fixed/random effect Panel Regression is used to check the underlined effect. The results reveal that Eid-ul-Fitr is the only Holy day, which has significant positive effect on stock returns of Asian markets, while all other Holy Days have no effect. Friday is the only Gregorian calendar anomaly, which exists in Asian markets. These results provide support to the fact that both Islamic and Gregorian calendar anomalies exist in Asian markets.
Keywords: G02; G14; Z1; 330; gregorian calendar anomalies; market efficiency; Holy Days; religion; Asian stock markets